1996
DOI: 10.1271/bbb.60.2059
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Lipase-catalyzed Preparation of Long-chain Fatty Acid Esters of Bile Acids: Biological Activity and Synthetic Application of the Products

Abstract: A highly regioselective (3-position) and efficient (quantitative yield) acylation of bile acids catalyzed by immobilized Candida antarctica lipase was established. Methyl cholate derivatives acylated with long-chain fatty acids (C12-C16) showed an inhibitory effect on the growth of some strains of Gram-positive and -negative bacteria (27-400 micrograms/ml). The anti-bacterial activity was slightly weaker than has been observed for methyl cholate, while the increased lipophilicity and lower melting points of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…Methyl cholate is the methyl ester form of cholic acid, inhibiting the synthesis of cholesterol [35]. It has been reported that methyl cholate suppresses the growth of certain Grampositive and Gram-negative bacteria [36] and has a good anti-inflammatory effect [37]. Biliverdin is a type of bile pigment, an oxidized product of heme.…”
Section: Discussionmentioning
confidence: 99%
“…Methyl cholate is the methyl ester form of cholic acid, inhibiting the synthesis of cholesterol [35]. It has been reported that methyl cholate suppresses the growth of certain Grampositive and Gram-negative bacteria [36] and has a good anti-inflammatory effect [37]. Biliverdin is a type of bile pigment, an oxidized product of heme.…”
Section: Discussionmentioning
confidence: 99%
“…22 Interestingly, CO 2 CH 3 groups at the 24-position, which are present in many of the substrates studied, are not reported to react. 21,22 They do, however, react under more vigorous conditions since when cholic acid ( 21) is treated with a relatively large amount of CALB in tetrahydrofuran at 50 C for 7 days oligomerization occurs, i.e. the 3a-hydroxyl groups and 24CO 2 H groups of different molecules react together.…”
Section: Introductionmentioning
confidence: 98%
“…In previously published work with bile acid derivatives it has been shown that 3a-hydroxyl groups are acetylated efficiently when treated with CALB and vinyl acetate in tetrahydrofuran. 21,22 No reaction occurs with 7a-, 7b-and 12a-hydroxyl groups: see formula 1 for the numbering of bile acid derivatives. [21][22][23] The 3a-hydroxyl group of methyl cholate (20) is also selectively acylated when treated with various methyl or vinyl alkanoates and CALB.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations